Extracellular-Added ADP-Ribose Increases Intracellular Free Ca2+ Concentration Through Ca2+ Release From Stores, but Not Through TRPM2-Mediated Ca2+ Entry, in Rat β-Cell Line RIN-5F - Ishii Masakazu; Shimizu Shunichi; Hagiwara Tamio; Wajima Teruaki; Miyazaki Akira; Mori Yasuo; Kiuchi Yuji (Journal of Pharmacological Sciences, 2006)
Abstract.: Intracellular ADP-ribose is an activator of TRPM2, which is a Ca2+-permeable channel and mediates H2O2-induced cell death, in the TRPM2-expressing rat β-cell line RIN-5F. We examined the effect of extracellular-added ADP-ribose on intracellular Ca2+ concentration in RIN-5F cells. ADP-ribose induced Ca2+ release from the thapsigargin-sensitive Ca2+ store, but not Ca2+ entry across the plasma membrane. A phospholipase C (PLC) inhibitor and a non-specific IP3 receptor inhibitor blocked its Ca2+ release. H2O2-induced Ca2+ entry through TRPM2 was not affected by extracellular ADP-ribose. These findings suggest that extracellular-added ADP-ribose induces Ca2+ release through the PLC-IP3 pathway and does not act as a TRPM2 activator. Keywords:: ADP-ribose, hydrogen peroxide, TRPM2